Effect of Primary Reference Fuel on Reactivity-Controlled Compression Ignition Engine Emission Produce - M. F., Zakiyuddin; Muthanna, Jamil; M. A., Hamidi; A. F., Yusop (Springer Nature, Singapore, 2023)
Reactivity-Controlled Compression Ignition or also known as RCCI mode engine is a modified of Homogeneous Charge Compression Ignition (HCCI) engine in which have a better control in combustion and wider load range. The strategies of RCCI mode in controlling the combustion is by using dual fuel of different reactivity such as diesel (high reactivity fuel) and gasoline (low reactivity fuel). The objective of this experimental investigation is to evaluate the effect of Primary Reference Fuel towards the emission produce by the RCCI engine mode. Single cylinder CI engine with port injection system is used in this study. Two alkane-based, iso-octane and n-heptane were blend together, PRF80 (80% iso-octane + 20% n-heptane) fuel mixtures were used throughout this study as low reactivity fuel in port injection system and pure diesel as high reactivity fuel in direct injection system. Result found that the performance of RCCI mode engine improve with the use of alkane (iso-octane and n-heptane) in the PRF80 blends especially in comparison to normal mode CI engine (using diesel only). In terms of emission, by using PRF80 in RCCI mode engine, the NOx reduce almost 95% of normal CI engine NOx production. As a result of applying PRF as a low reactivity fuel in an RCCI engine system, knocking resistance may be produced even at high engine compression ratios, resulting in better thermal efficiency and reduced NOx-Soot emissions.